2021
DOI: 10.1088/1741-2552/ac1037
|View full text |Cite
|
Sign up to set email alerts
|

Automated pipeline for EEG artifact reduction (APPEAR) recorded during fMRI

Abstract: Objective. Simultaneous electroencephalography-functional magnetic resonance imaging (EEG-fMRI) recordings offer a high spatiotemporal resolution approach to study human brain and understand the underlying mechanisms mediating cognitive and behavioral processes. However, the high susceptibility of EEG to MRI-induced artifacts hinders a broad adaptation of this approach. More specifically, EEG data collected during fMRI acquisition are contaminated with MRI gradients and ballistocardiogram ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…We found that, even though a clear reduction of the artifact was observed on the power spectra of our rs-EEG-fMRI data, none of the BCG artifact removal approaches tested (AAS, OBS, ICA, OBS-ICA, AAS-ICA, PROJIC-AAS, PROJIC-OBS) entirely preserved the spectral profile of EEG signals, due to both artifact residuals and induced EEG signal losses. Overall, in line with previous reports (Srivastava et al, 2005;Debener et al, 2006;Mayeli et al, 2021), we found better results with ICA-based approaches, especially when used after AAS or OBS, as compared to the conventional AAS and OBS and PROJIC approaches. Additionally, large variability in the artifact correction outcomes was observed, with some subjects even showing decreased absolute power compared to their outside rs-EEG, which may be reflecting EEG signal losses after the artifact correction procedure (Ullsperger and Debener, 2010;Marino et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that, even though a clear reduction of the artifact was observed on the power spectra of our rs-EEG-fMRI data, none of the BCG artifact removal approaches tested (AAS, OBS, ICA, OBS-ICA, AAS-ICA, PROJIC-AAS, PROJIC-OBS) entirely preserved the spectral profile of EEG signals, due to both artifact residuals and induced EEG signal losses. Overall, in line with previous reports (Srivastava et al, 2005;Debener et al, 2006;Mayeli et al, 2021), we found better results with ICA-based approaches, especially when used after AAS or OBS, as compared to the conventional AAS and OBS and PROJIC approaches. Additionally, large variability in the artifact correction outcomes was observed, with some subjects even showing decreased absolute power compared to their outside rs-EEG, which may be reflecting EEG signal losses after the artifact correction procedure (Ullsperger and Debener, 2010;Marino et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Several signal processing tools have been developed to deal with the BCG artifact and reduce its contribution from the recordings while preserving EEG signal properties (Bullock et al, 2021;Ebrahimzadeh et al, 2022). As summarized in Bullock et al (2021) the most popular BCG correction approaches include Average Artifact Subtraction (AAS); (Allen et al, 1998), Optimal Basis Set (OBS); (Niazy et al, 2005), Independent Component Analysis (ICA); (Srivastava et al, 2005) and the combination of these: OBS-ICA (Debener et al, 2006) and AAS-ICA (Mayeli et al, 2021). Some other methods have also been recently proposed including the PROJIC-AAS and PROJIC-OBS methods (Abreu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, MRI imaging artifacts within the EEG signal were reduced using the average artifact subtraction (AAS) method [54]. After downsampling EEG signals to 250 Hz, band-rejection filters with 1 Hz bandwidth [55][56][57] were applied to reduce fMRI slice selection fundamental frequency (19.5 Hz) and its harmonics, mechanical vibration noise (26 Hz) along with an alternating current power line noise (60 Hz). Another bandpass filter from 0.1 to 80 Hz (48 dB/octave) was applied to the EEG data.…”
Section: Eeg Data Preprocessingmentioning
confidence: 99%
“…Most prior studies used variations of AAS, which leaves substantial residual artifact. A few studies have also used a related independent component analysis-based method (Mayeli et al, 2021(Mayeli et al, , 2016. These existing online BCG artifact reduction techniques, while helpful, do not perform as well as reference-based methods (Hermans et al, 2016), and a better solution is required if real-time EEG-fMRI (rtEEG-fMRI) is to see more widespread adoption (Warbrick, 2022).…”
Section: Introductionmentioning
confidence: 99%